Criminal law measures to combat crimes related to organized crime (Journal of actual problems of jurisprudence, 2018)
Presented article is the result of a comprehensive study conducted by the author. In this article, the author examines the issues related to organized crime. This question is of particular importance in connection with the trend increase in the number of crimes committed by an organized group. These facts necessitate the study of issues of crime groups and measures to counter it.Key words: crimes, gang, society, people, organized crime group.